Implementasi Pendidikan dan Pelatihan Kepala Sekolah di Dinas Pendidikan dan Kebudayaan Kabupaten Mamasa - Habibah, Sitti; Wahira, Wahira; Syam, Sriwidayani; Seprianto, Virgo (INSIGHT: Indonesian Journal Social Studies and Humanities, 2024)
Abstract. This research examines the implementation of education and training for school principals at the Mamasa Regency Education and Culture Office. The aim of this research is to determine the description of the implementation of education and training for school principals within the Mamasa Regency Education and Culture Office. This research approach is descriptive qualitative with a phenomenological type. This research was carried out at the Mamasa Regency Education and Culture Office, West Sulawesi Province. The data sources in this research are the Head of Department, Teacher and Education Personnel Development Sector and School Principals, data collection techniques in the form of observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions, checking the validity of the data using the triangulation method. The results of the research show that the implementation of education and training for school principals is quite optimal and has contributed well to increasing the competence of school principals, and the process has taken place effectively and efficiently, which includes 5 implementation steps, namely the process of analyzing education and training needs (Training Need Assessment). , establishing education and training objectives, curriculum development and determination of training components, preparation and implementation of training, and evaluation of education and training. Supporting factors in the implementation of training are resource persons who are competent and experts in their fields as well as adequate facilities. The inhibiting factors include regional geographical conditions, ability to use technology, and budget limitations. Keywords : School Principal Education and Training